DESIGN DAN ANALISIS LIFTING ARRANGEMENT YANG OPTIMAL UNTUK PENGANGKATAN PROJECT MODUL BERRI BERLOKASI DI PERUSAHAAN SAIPEM TAQA AL-RUSHAID YARD - Angga Franciska; Trisno Susilo; Zakwan Hilmy (Fakultas Sains dan Teknologi Universitas Karimun, 2020)
Lifting Arrangement is a platform for the process of using cranes, in this final task discussing the operation of a platform located in the main deck conducted in Saipem Taqa Al-Rushaid Yard Company. The analysis of this research is focused on the Penganangkatan tool because it has different types and types. The size of the Platform has a length of 34714 m, width of 18700 m and weight 221.51 tonnes. The most critical part of this lifting process is the angle determination for each wire sling because the crane is used for different types and types. The Minimum Angel used in the process of the Pengkatan this platform for Crane 1 is 69 º, Crane 2 is 69 º, Crane 3 is 71 º and the Crane 4 is 71 º.